1986
DOI: 10.1126/science.3003917
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Incidence of AIDS in Five Cohorts of HTLV-III-Infected Risk Group Members

Abstract: The incidence of the acquired immune deficiency syndrome (AIDS) among persons infected with human T-lymphotropic virus type III (HTLV-III) was evaluated prospectively among 725 persons who were at high risk of AIDS and had enrolled before October 1982 in cohort studies of homosexual men, parenteral drug users, and hemophiliacs. A total of 276 (38.1 percent) of the subjects were either HTLV-III seropositive at enrollment or developed HTLV-III antibodies subsequently. AIDS had developed in 28 (10.1 percent) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…As reported in different cohorts around the world, many patients with hemophilia became infected with HIV between 1982 and 1985. In some hemophilic populations, subsequent testing of stored frozen plasma samples revealed that the first infections with HIV occurred in 1978-79, that the bulk of patients were infected in 1981-82, and that there were very few new infections by the end of 1984 (Eyster, 2008;Goedert et al, 1985). The HCV epidemic was a much longer one, occurring between 1961 and 1985.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in different cohorts around the world, many patients with hemophilia became infected with HIV between 1982 and 1985. In some hemophilic populations, subsequent testing of stored frozen plasma samples revealed that the first infections with HIV occurred in 1978-79, that the bulk of patients were infected in 1981-82, and that there were very few new infections by the end of 1984 (Eyster, 2008;Goedert et al, 1985). The HCV epidemic was a much longer one, occurring between 1961 and 1985.…”
Section: Introductionmentioning
confidence: 99%
“…It is on the basis of the relatively high conversion rates of these risk groups that every asymptomatic infection by HIV is now being called "HIV disease" (7), and that some are subjected to chemotherapy (39). Nevertheless, individual asymptomatic periods are unpredictable, ranging from <1 to >15 years (22,(33)(34)(35)(36)(37)(38). Once AIDS is diagnosed, the mean life expectancy is about 1 year (35).…”
mentioning
confidence: 99%
“…Moreover, the AIDS risk of an antibody-positive American varies a great deal with his or her risk group. For example, 3-25% of antibody-positive Americans who habitually practice risk behavior or are hemophiliacs develop AIDS annually (7,21,22,(33)(34)(35)(36)(37)(38). Thus, the 1.5% annual conversion rate of antibody-positive Americans is an average of minorities with high conversion rates of 3-25% and a majority with a conversion rate close to %o.…”
mentioning
confidence: 99%
“…HIV infection is characterized by a prolonged period of latency, which may be followed by AIDS or AIDS-related complex (Goedert et al, 1986). Progression to AIDS has been associated with the detection of HIV core antigen in serum Lange et al, 1986) indicating a role for enhanced HIV gene expression in the pathogenesis of HIV.…”
mentioning
confidence: 99%